2019
DOI: 10.1213/ane.0000000000003888
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Echocardiography for Patients With Hip Fractures Undergoing Surgery: A Retrospective Cohort Study Using a Nationwide Database

Abstract: BACKGROUND: The effect of preoperative transthoracic echocardiography on the clinical outcomes of patients with hip fractures undergoing surgical treatment remains controversial. We hypothesized that preoperative echocardiography is associated with reduced postoperative morbidity and improved patient survival after surgical repair of hip fractures. METHODS: Drawing from a nationwide administrative database, patients undergoing hip fracture surgeries bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…24 The in-hospital mortality rate was 2.8% in our study, which is in agreement with a previous study result. 25 Both AS and LVEF <50% were independent predictors of inhospital mortality. AS was established as an important factor that was associated with higher mortality in previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…24 The in-hospital mortality rate was 2.8% in our study, which is in agreement with a previous study result. 25 Both AS and LVEF <50% were independent predictors of inhospital mortality. AS was established as an important factor that was associated with higher mortality in previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies since 2011 have provided conflicting results on outcome benefits and treatment decisions after pre‐operative (focused) transthoracic echocardiography in hip fracture patients [54–56]. Group separation in a recent pilot study suggests that a larger, multicentre RCT comparing mortality/composite outcomes after focused echocardiography is feasible [57, 58].…”
Section: Controversiesmentioning
confidence: 99%
“…Current guidelines recommend that preoperative echocardiography be performed for patients with clinically suspected moderate or severe valvular stenosis or regurgitation 4 , 5 ; however, the necessity of preoperative echocardiography in patients with high cardiac risk is still a matter of debate. A recent study reported that heart failure defined by left ventricular ejection fraction < 50% was significantly associated with 90-day mortality after noncardiac surgery regardless of clinical symptoms 38 ; however, another study reported that preoperative echocardiography was not linked to decreased postoperative complications or in-hospital mortality after hip fracture surgery 39 . Randomized trials are needed to assess the potential benefits of preoperative echocardiography in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%